Improving change analysis from near-continuous 3D time series by considering full temporal information [data and source code] - Anders, Katharina; Winiwarter, Lukas; Höfle, Bernhard (Universität, 2021)
This dataset comprises the source code (Python scripts) and data to perform spatiotemporal segmentation in time series of surface change data for a...
Gesehen am 13.12.2021
Keywords: Forschungsdaten; Datenbank